2016
DOI: 10.1002/tkm2.1058
|View full text |Cite
|
Sign up to set email alerts
|

Elevated direct bilirubin: Possible predictors for pseudoaldosteronism: Case–control study

Abstract: Aim: Pseudoaldosteronism is a known side-effect of licorice, and Japanese traditional Kampo medicine is one of the major areas of use of licorice in Japan. Multidrug resistance protein 2 (Mrp2) dysfunction is important for pseudoaldosteronism. Congenital deficiency of Mrp2 causes constitutional jaundice with elevated direct bilirubin. Hence, elevated direct bilirubin can be a biomarker of Mrp2 dysfunction. The relationship between pseudoaldosteronism and elevated direct bilirubin, however, has not been studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Since 99.9% of circulating GA are bound to albumin, 29 hypoalbuminaemia may increase the unbound fraction of GA through pharmacokinetic alteration, resulting in an enhancement of the pharmacological actions of GA. Yoshino and colleagues have suggested that hypoalbuminaemia was a risk factor for pseudoaldosteronism in three other Kampo-medicines. 30 The present results are the first to report that hypoalbuminaemia is a possible risk factor for liquorice-induced hypokalaemia due to YK preparations.…”
Section: Discussionmentioning
confidence: 47%
“…Since 99.9% of circulating GA are bound to albumin, 29 hypoalbuminaemia may increase the unbound fraction of GA through pharmacokinetic alteration, resulting in an enhancement of the pharmacological actions of GA. Yoshino and colleagues have suggested that hypoalbuminaemia was a risk factor for pseudoaldosteronism in three other Kampo-medicines. 30 The present results are the first to report that hypoalbuminaemia is a possible risk factor for liquorice-induced hypokalaemia due to YK preparations.…”
Section: Discussionmentioning
confidence: 47%
“…We used the cut‐off values applied by the Department of Laboratory Medicine at Keio University Hospital. We also applied additional conditions for each definition according to our previous report . An elevated D‐Bil level was defined as the presence of ≥2 readings of ≥0.3 mg/dL during the study period.…”
Section: Methodsmentioning
confidence: 99%
“…Dubin‐Johnson syndrome involves congenital dysfunction of Mrp2 and is characterized by elevated D‐Bil levels . We published a small retrospective cohort study that described patients with probable pseudoaldosteronism who also had elevated D‐Bil levels …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, hypoalbuminemia may be an important risk factor for PsA. Indeed, hypoalbuminemia has been identified as a risk factor in patients receiving yokukansan, which contains 1.5 g of licorice daily (49), as well as in other case series (50,51).…”
Section: Distributionmentioning
confidence: 99%
“…When bile excretion of GA3S is suppressed due to Mrp2 dysfunction (Figure 2), GA3S is transferred into the blood circulation. We have previously highlighted the involvement of Mrp2 in the biliary excretion of GL metabolites in rats (27,34,35) and possibly in humans (50,51). GL metabolites significantly accumulate in the EHBR (27,34,35).…”
Section: Excretionmentioning
confidence: 99%